2017
DOI: 10.1159/000479386
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Anaphylaxis and Atopic Dermatitis to Salt-Soluble Wheat Protein Extract

Abstract: Background: Wheat allergy and other immune-mediated disorders triggered by wheat proteins are growing at an alarming rate for reasons not well understood. A mouse model to study hypersensitivity responses to salt-soluble wheat protein (SSWP) extract is currently unavailable. Here we tested the hypothesis that SSWP extract from wheat will induce sensitization as well as allergic disease in mice. Methods: Female BALB/cJ mice were weaned onto a plant protein-free diet. The mice were injected a total of 4 times wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…Temperature was measured every 5 to 15 minutes with a rectal probe. Previous publications have shown that the development of hypothermia correlates with mast cell degranulation in murine IgE-mediated anaphylaxis by demonstrating (1) a correlation between degree of hypothermia and mouse mast cell protease 1 (MMCP-1) responses; [26][27][28] (2) the failure of mast cell-deficient mice to develop hypothermia in response to cross-linking of IgE; 6 and (3) the importance of histamine in IgE-mediated anaphylaxis. 6…”
Section: Detection Of Systemic Anaphylaxismentioning
confidence: 99%
“…Temperature was measured every 5 to 15 minutes with a rectal probe. Previous publications have shown that the development of hypothermia correlates with mast cell degranulation in murine IgE-mediated anaphylaxis by demonstrating (1) a correlation between degree of hypothermia and mouse mast cell protease 1 (MMCP-1) responses; [26][27][28] (2) the failure of mast cell-deficient mice to develop hypothermia in response to cross-linking of IgE; 6 and (3) the importance of histamine in IgE-mediated anaphylaxis. 6…”
Section: Detection Of Systemic Anaphylaxismentioning
confidence: 99%
“…As discussed in the introduction, salt-soluble wheat proteins (SSWPs) are also important allergens in wheat allergic humans [44]. Therefore, Jin et al (2017) tested whether SSWPs can elicit allergic disease in Balb/c mice similar to humans (Table 2 and Table 4) [45]. They found that: (i) SSWP elicits robust IgE responses and sensitization, and mice show anaphylaxis when challenged; (ii) they showed for the first time that in this mouse model, anaphylaxis is linked to IgE-mediated mucosal mast cell degranulation [45,46]; and (iii) interestingly, some of the wheat allergic mice (but not all) developed atopic dermatitis lesions on the face, showing extensive mast cell degranulation and elevated levels of pro-inflammatory and allergic chemokines and cytokines (Table 2 and Table 4).…”
Section: Insights In To the Molecular Mechanisms Of Wheat Allergenmentioning
confidence: 99%
“…There are conflicting reports of whether B10.A does or does not develop an IgE response to gliadins [27,28]. In particular, Balb/c mice show immune responses that are remarkably similar to that of wheat allergic humans [30,45]. Interestingly, C3H/Hej mice, which are popular peanut allergy models, do not develop a gliadin allergy, suggesting the possibility of genetic resistance [30].…”
Section: Insights In To the Molecular Mechanisms Of Wheat Allergenmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved and novel models to study the disease will also contribute to further developing alternative treatment [46]. …”
Section: Atopic Dermatitismentioning
confidence: 99%